Fiber-based quantum-dot pulse oximetry for wearable health monitoring with high wavelength selectivity and photoplethysmogram sensitivity - Ho Seung Lee; Byeongju Noh; Seong Uk Kong; Yong Ha Hwang; Ha-Eun Cho; Yongmin Jeon; Kyung Cheol Choi (npj Flexible Electronics, 2023)
Abstract Increasing demand for real-time healthcare monitoring is leading to advances in thin and flexible optoelectronic device-based wearable pulse oximetry. Most previous studies have used OLEDs for this purpose, but did not consider the side effects of broad full-width half-maximum (FWHM) characteristics and single substrates. In this study, we performed SpO2 measurement using a fiber-based quantum-dot pulse oximetry (FQPO) system capable of mass production with a transferable encapsulation technique, and a narrow FWHM of about 30 nm. Based on analyses we determined that uniform angular narrow FWHM-based light sources are important for accurate SpO2 measurements through multi-layer structures and human skin tissues. The FQPO was shown to have improved photoplethysmogram (PPG) signal sensitivity with no waveguide-mode noise signal, as is typically generated when using a single substrate (30–50%). We successfully demonstrate improved SpO2 measurement accuracy as well as all-in-one clothing-type pulse oximetry with FQPO.